2020
DOI: 10.1001/jamanetworkopen.2020.19795
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Ethnicity With Comorbidities and Survival Among Patients With COVID-19 at an Urban Medical Center in New York

Abstract: IMPORTANCE As of May 11, 2020, there have been more than 290 000 deaths worldwide from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19). Risk-adjusted differences in outcomes among patients of differing ethnicity and race categories are not well characterized. OBJECTIVES To investigate whether presenting comorbidities in patients with COVID-19 in New York City differed by race/ethnicity and whether case fatality rates varied among different ethnic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
205
5
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(232 citation statements)
references
References 8 publications
12
205
5
10
Order By: Relevance
“…During the initial peak of the COVID-19 pandemic, the decision to cease all elective surgery was driven by both a dearth of resources and a desire to limit exposure of new patients. All resources at MMC were redirected to the care of the over 5000 patients who presented for treatment tested positive for COVID-19 [ 12 ]. Furthermore, it was challenging to perform elective procedures in a way that was safe for both patients and providers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the initial peak of the COVID-19 pandemic, the decision to cease all elective surgery was driven by both a dearth of resources and a desire to limit exposure of new patients. All resources at MMC were redirected to the care of the over 5000 patients who presented for treatment tested positive for COVID-19 [ 12 ]. Furthermore, it was challenging to perform elective procedures in a way that was safe for both patients and providers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant associations between obesity and severe COVID-19 disease, especially in patients in the Bronx at our own healthcare system, the patients in our study had extremely good outcomes [ 12 ]. None of our patients who reported symptoms or were diagnosed with COVID-19 had severe symptoms or was admitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our meta-analysis suggested that Hispanic patients may have better prognosis compared to non-Hispanic white, the impact of ethnicity on the prognosis of COVID-19 is yet to be explained. While a regional study from the United States reported that ethnicity may be a factor for diverse outcomes [114], other studies denied these ndings after adjusting for risk factors [115,116]. A recent meta-analysis of has suggested that, after adjusting patient characteristics, ethnicity may not be an independent prognostic factor [117].…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality rates between white American and African American patients who received hospital treatment showed no statistically significant difference [ 89 ]. Similarly, no differences were found between Hispanics, African Americans, non-Hispanics, and Asians [ 90 ].…”
Section: Covid-19 and Social Injusticementioning
confidence: 99%